Glucuronoyl esterases – enzymes to decouple lignin and carbohydrates and enable better utilization of renewable plant biomass. Issue 3 (18th April 2023) - Larsbrink, Johan; Lo Leggio, Leila
Abstract: Glucuronoyl esterases (GEs) are microbial enzymes able to cleave covalent linkages between lignin and carbohydrates in the plant cell wall. GEs are serine hydrolases found in carbohydrate esterase family 15 (CE15), which belongs to the large α/β hydrolase superfamily. GEs have been shown to reduce plant cell wall recalcitrance by hydrolysing the ester bonds found between glucuronic acid moieties on xylan polysaccharides and lignin. In recent years, the exploration of CE15 has broadened significantly and focused more on bacterial enzymes, which are more diverse in terms of sequence and structure to their fungal counterparts. Similar to fungal GEs, the bacterial enzymes are able to improve overall biomass deconstruction but also appear to have less strict substrate preferences for the uronic acid moiety. The structures of bacterial GEs reveal that they often have large inserts close to the active site, with implications for more extensive substrate interactions than the fungal GEs which have more open active sites. In this review, we highlight the recent work on GEs which has predominantly regarded bacterial enzymes, and discuss similarities and differences between bacterial and fungal enzymes in terms of the biochemical properties, diversity in sequence and modularity, and structural variations that have been discovered thus far in CE15.